2005
DOI: 10.1002/app.21020
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale morphological analysis of commingled PP/unidirectional glass fiber composites: Experiment and theory

Abstract: Quantitative 2D image processing has been performed to assess the morphology of commingled polypropylene composites reinforced by a range of glass fiber contents. Quantitative morphological probes, derived from both local and global analyses, point out the heterogeneous dispersion of unidirectional fibers within the polymer matrix, i.e., the presence of aggregates. It is found that more than 86% of fibers are packed into aggregates at a maximum packing fraction of 0.84 whatever the filler content. Moreover, ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…On the basis of viscoelastic properties of aggregates, the prediction of the mechanical behavior of unidirectional composites can now be determined. A previous morphological analysis has shown that fiber aggregates are randomly dispersed within the polymer matrix, whatever the content of fillers 19…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…On the basis of viscoelastic properties of aggregates, the prediction of the mechanical behavior of unidirectional composites can now be determined. A previous morphological analysis has shown that fiber aggregates are randomly dispersed within the polymer matrix, whatever the content of fillers 19…”
Section: Resultsmentioning
confidence: 96%
“…Using a 2D image processing, Dubouloz‐Monnet et al19 have shown that the composites exhibit a heterogeneous morphology characterized by both isolated fibers and aggregates. In fact, more than 86% of glass fibers are packed into aggregates randomly dispersed within the polymer matrix.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average diameters of E-glass and iPP fibers are 17.5 and 30 µm, respectively. 17 TWINTEX plies can be formed into rigid laminates under the simultaneous application of heat and pressure. According to technical datasheets from Vetrotex, the compacted material has an average tensile modulus of 13.8 GPa and a tensile strength of 280 MPa.…”
Section: Methodsmentioning
confidence: 99%